Comparative study of the immunomodulatory effect of solar and photonically inactivated salmonella enteritidis on dendritic cells in-vitro - Adeniran, Dorcas Oluwaseun Taiwo (Vaal University of Technology, 2022)
Salmonellosis is a food and water-borne disease that affects humans, especially those that are immunocompromised as well as children and the elderly. This disease is caused by a variety of Salmonella species. Salmonella Enteritidis (SE) is the most frequently isolated serovar in infections occurring in humans and from animals all over the world. Salmonella Enteritidis is found in many animals and can survive in environmental samples for several weeks under ideal conditions. The failure of waste water treatment plants, agricultural pollution, and storm water runoff into natural water sources has led to an increase in the presence of Salmonella in water. The possibility of fecal contamination of water remains high in resource poor communities where sanitary and hygienic practices are inefficient or insufficient. However, many resource poor communities are using solar disinfection (SODIS) as a means of treating water prior to consumption. The SODIS method is achieved by exposing bacterial contaminated water to the sun for the period of 6 to 8 hours. The reliability of the SODIS process depends on factors such as temperature, dissolved oxygen and most importantly UV-A radiation. These factors cannot be controlled in a natural environment due to fluctuations or climatic changes in weather conditions. Instead of relying only on SODIS, other methods such as the use of a photonic device to disinfect microbiologically water are being used. The main aim of this study is to compare the immunomodulatory effect of solar irradiated and photonically inactivated S. Enteritidis on dendritic cells in-vitro and to provide supporting information on the immunological benefits on the consumers of SODIS drinking water through a SODIS mimicking device. To achieve this aim, there was a need to optimize the SODIS and photonic inactivation conditions of S. Enteritidis. Salmonella Enteritidis cultures were exposed to solar irradiation during spring, summer and winter as well as photonically using an ultraviolet light. The result revealed that the inactivation efficiency of Solar ultraviolet radiation (SUVR) on S. Enteritidis was season dependent. A total loss of activity was observed in S. Enteritidis during summer and no regrowth was observed. With the photonic device, a combination of UV and oxygen inactivated the S. Enteritidis to below detectable limits. This study compared the protein profiles of solar irradiated and photonically inactivated S. Enteritidis using SDS-PAGE. The results showed a gradual decrease in the concentration of the protein banding patterns with time in S. Enteritidis that was either solar irradiated or photonically inactivated. The ability of the solar and photonically inactivated S. Enteritidis to induce maturation of dendritic cells in-vitro was also investigated. There was a significant increase in CD80 when the 8-hour solar inactivated samples of S. Enteritidis was used to stimulate the dendritic cells. The higher levels of co-stimulatory molecules observed suggested the possible involvement of these molecules in antigen uptake and presentation to produce a specific immune response. This finding will contribute towards the understanding of the immunological effects that may be generated from consuming SODIS water and whether it may result in an immune reaction or response. Although the current study shows that solar irradiated and photonically inactivated cultures of S. Enteritidis were able to induce the expression of key immunological surface makers by dendritic cells, further studies are required to corroborate the findings of this study.
M (ASB) (Biotechnology, Department of Chemistry and Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Immunomodulatory effect of solar and photonically; Salmonellosis; Salmonella Enteritidis (SE); Water and agricultural pollution; Solar disinfection (SODIS); Dissertations, Academic -- South Africa.; Bacterial genetics.; Microbial genetics.; Salmonella infections.; Salmonella.; Vaccination.